Anna and the king - Tennant, Andy; Foster, Jodie; Chow Yun Fat (Fox 2000 Pictures, 2000)
When English schoolteacher, Anna Leonowens, arrives in the exotic land of Siam to teach the children of king Mongkut, her Western sensibilities clash with the ruler's Eastern ways. The tension build as Mongkut learns that outside forces are conspiring against his regime. With the political intrique set to explode. Anna and the King must become allies in a daring fight to save Siam from dangerous enemies bent on destruction.